The incidence, prevalence, and years lived with disability of forearm fractures: a systematic analysis based on the global burden of disease study 2021 - Fan, Xiaobo; Yang, Zongyou; Liu, Yuan; Wei, Zhikun; Zhao, Chenyang; Pang, Chaojian (Frontiers in Public Health, 2025)
PurposeForearm fractures significantly impact global health and socioeconomic systems. This study examines forearm fracture burden across 204 countries and territories from 1990 to 2021.MethodsData from Global Burden of Disease (GBD) 2021 were analyzed, including incidence (new cases occurring each year), prevalence (total existing cases at a given time), years lived with disability (YLDs, measuring time lived with reduced health due to injury), and causes categorized by injury mechanisms. Age-standardized rates (ASRs) with 95% uncertainty intervals (UIs) were calculated to address demographic variability. Trends were stratified by region, age, sex, and injury etiology.ResultsGlobally, forearm fracture cases increased by 22.25% (from 26.1 to 31.9 million), while age-standardized incidence rates declined by 16.75% (to 402.35 per 100,000). Prevalence rose by 39.12% (from 4.5 to 6.2 million cases), with YLDs increasing by 42.22% (from 144,166 to 205,031). Regional variations were substantial: Oceania experienced the highest incidence surge (150%), whereas Central Europe saw a 32.17% decline. Sex-specific analysis revealed marked disparities: in the ≥75 age groups, female prevalence rates were approximately double those of males (>800 per 100,000 vs. 300 per 100,000 for ages 95+). Among the older adult (≥60 years), females showed a steeper increase in YLD rates, reaching 30 per 100,000 in the 95 + age group compared with 15 per 100,000 in males. Falls were the predominant cause, particularly in Central/Eastern Europe (>500 per 100,000).ConclusionDespite declining age-standardized rates, the absolute cases of forearm fractures is rising due to population aging and uneven healthcare access. Sex-specific prevention strategies are needed, emphasizing osteoporosis screening for postmenopausal women and workplace safety measures in regions with high mechanical-force injuries. Policymakers should prioritize resources for high-burden regions and implement targeted fall prevention programs.